Growth hormone, enhancement and the pharmaceuticalisation of short stature. (April 2015) - Morrison, Michael
Abstract: This paper takes the biological drug human Growth Hormone (hGH) as a case study to investigate processes of pharmaceuticalisation and medicalisation in configuring childhood short stature as a site for pharmaceutical intervention. Human growth hormone is considered to have legitimate applications in treating childhood growth hormone deficiency and short stature associated with other recognised conditions. It is also regarded by bioethicists and others as a form of human biomedical enhancement when applied to children with idiopathic or 'normal' short stature. The purpose of this study is not to evaluate whether treatment of idiopathic short stature is enhancement or not, but to evaluate how some applications of hGH in treating short stature have come to be accepted and stabilised as legitimate 'therapies' while others remain contested as 'enhancements'. A comparative, historical approach is employed, drawing on approaches from medical sociology and Science and Technology Studies (STS) to set out a socio-technical history of hGH in the US and UK. Through this history the relative influence and interplay of drivers of pharmaceuticalisation, including industry marketing and networks of drug distribution, and processes of medicalisation will be employed to address this question and simultaneously query the value of enhancement as a sociological concept. Highlights: Takes human Growth Hormone (hGH) as a historical case study of human enhancement. Investigates enhancement in terms of pharmaceutical and medicalising processes. Demonstrates dynamic interaction between these processes in the case of hGH. Challenges normatively-loaded bioethical concept of human enhancement. Highlights academic medical research as a driver of pharmaceuticalisation.